1970
DOI: 10.3329/ptcb.v18i2.3649
|View full text |Cite
|
Sign up to set email alerts
|

Thymol Production from Callus Culture of Nigella sativa L.

Abstract: Roots, hypocotyls and leaves of Nigella sativa L. were collected from the seedlings raised on sterilized filter paper and cultured on MS supplemented with different concentrations of 2,4-D (0.0, 1.0, 2.0, 3.0, 4.0 mg/l) and Kn (0.0, 1.0, 1.5, 2.0, 2.5, 3.0, 5.0). The best callus production was obtained from leaf explants with 1 mg/l 2,4-D and 1.5 mg/l Kn. The higher thymol concentrations were extracted after 75 days for the above callus; which was detected by HPLC using retention time. This is the first report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…High callus formation was achieved from high-auxin-containing media, and auxincytokinin content balanced mediums. When similar previous studies were examined, a high rate of callus formation was obtained in cases where the mediums which had auxin-cytokinin were balanced and had high auxin content, similar to the results obtained from this study (AL-ANI, 2008;CHAUDHRY and AHMAD, 2013;QAMAR and SHIREEN, 2016). Callus formation was observed in almost all of the explants subject to this research in the medium containing 2.4-D, which is auxin hormone.…”
Section: Resultssupporting
confidence: 87%
“…High callus formation was achieved from high-auxin-containing media, and auxincytokinin content balanced mediums. When similar previous studies were examined, a high rate of callus formation was obtained in cases where the mediums which had auxin-cytokinin were balanced and had high auxin content, similar to the results obtained from this study (AL-ANI, 2008;CHAUDHRY and AHMAD, 2013;QAMAR and SHIREEN, 2016). Callus formation was observed in almost all of the explants subject to this research in the medium containing 2.4-D, which is auxin hormone.…”
Section: Resultssupporting
confidence: 87%
“…Based on Table 5 showed that flavonoid content from callus culture lower than leaves of black cumin. Callus produced in vitro can be understood due to the production of metabolites secondary in vitro callus is influenced by various factors including the composition of the medium used and the applied growth regulator [2,[8][9].…”
Section: Flavonoid Contentmentioning
confidence: 99%
“…As an herbal plant, the seeds of black cumin are able to overcome various types of diseases including viruses. According to [2,3] black cumin has many benefits in overcoming various diseases such as anticancer, immunity-enhancing, antihistamine, anti-inflammatory, microbial and anti-tumour activity. Black cumin also contains secondary metabolite compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Chaudhry et al and Hoseinpanahi et al concluded that combination of Kn + NAA and BAP + IAA enhanced terpenoid and thymol production in suspension culture of N. sativa [72,73]. Al-Ani also reported that 2,4-D and Kn initiated callus formation from leaf explant of Nigella sativa with enhanced thymol concentration [74]. By enhancing metabolic content the antioxidant activity of culture is also increased, Further, TDZ + NAA enhanced biomass and antioxidant activity of callus of Nigella sativa [77].…”
Section: Effects Of Pgrsmentioning
confidence: 99%
“…Some recent examples of medicinal secondary metabolites in suspension cultures include zerumbone production in Zingiber zerumbet, [102] ursolic acid production in Eriobotrya japonica, [103] lutein and tocopherol in carrot, [104] rosmarinic acid in Satureja khuzistanica [105] and taxane in Taxus chinensis [106], enhanced terpenoid and thymol production in N. sativa [72]. Al-Ani reported that from callus culture of N. sativa higher thymol concentration was extracted [74]. Enhanced biomass and antioxidant activity showed by the Cotyledon derived callus culture of Nigella sativa [77].…”
Section: Plant Cell Cultures Strategies For Phytochemical Productionmentioning
confidence: 99%